TEKNOLOGI PERTANIAN SEMI-ORGANIK PADA USAHATANI PADI: SUATU TINJAUAN DARI PERSPEKTIF ANALISIS INCREMENTAL BENEFIT-COST RATIO - Septiadi, Dudi; Tajidan, Tajidan; Wulandari, Wizatul Ika (AGROTEKSOS; Vol 33 No 1 (2023): Jurnal Agroteksos April 2023DO - 10.29303/agroteksos.v33i1.826, 2023)
The evaluation of the viability of agriculture through the analysis of the R/C ratio is considered inappropriate in the application of new technology. The analysis tool that is considered adequate is the incremental benefit-cost ratio (IBCR). The objective of the research was to determine the effect of the application of semi-organic agricultural technology on production and to research objective was to determine the effect of semi-organic agricultural technology on production and achieve the research objectives, the research was carried out in 40 rice farming units in Pringgasela district, East Lombok Regency. The survey was conducted in rice farms applying semi-organic agriculture technology and farms applying non-organic agriculture technology during the planting season of 2022. In each group of farmers, there are 20 units of rice farming applied semi-organic technology, and 20 units applied semiorganic technology. Sampling used a quota sampling technique and data were analyzed using IBCR. The results showed that the application of semi-organic technology in rice farming had a negative impact on rice production and was not economical (not feasible) to be applied to rice farming in the tropics with an IBCR value of <1.00, due to the application of semi-organic agricultural technology to rice farming negative impact on rice production, as well as providing lower economic benefits compared to nonorganic farming technologies.